Recent progress in cassava agronomy research in Vietnam - Nguyen, Huu Hy; Tran, Dai Nghia; Pham, Van Bien (International Center for Tropical Agriculture, 1995)
Cassava is an important root crop in Vietnam, and after rice and maize it is the major source of calories for human consumption and animal feed. Recently, cassava research has been supported by the national Root and Tuber Crops Resarch Program and by CIAT. Cassava agronomy research has produced the following results: - Among various intercropping systems, the interplanting of cassava with peanut, mungbean or maize were the most promising in the South, while intercropping with peanut was most promising in the North. - Cassava planted vertically and on single ridges gave higher yields than planting in other positions or with other types of plant bed configurations. Differences in yield due to stake position or plant bed configuration were not significant, however. - Long-term NPK trials showed that in Hung Loc Center in Dong Nai there was still no response of cassava to fertilizers after three years of continuous cropping, while in Agric. College #3 in Bac Thai highly significant responses to N, P and K were already observed in the first year